Relation Between The Incidence Of Bullying and Student Assertive Behavior in SMA Negeri 4 Denpasar - Putu Venessa (Politeknik Kesehatan Kartini Bali, 2020)
Bullying is an act of intimidation or harassment both physically and psychologically unreasonable from individuals or groups to other individuals from time to time and continues to create a pattern of harassment against individuals who cannot defend themselves.3 One of the factors that identifies the tendency to become victims of bullying is assertiveness. In this case, it is necessary to instill assertive behavior in every teenager so that they can express themselves without offending others. In this study, the researcher wanted to see a relationship between the incidence of bullying and assertive behavior among students at SMA Negeri 4 Denpasar. This study uses data collection techniques by distributing questionnaires to students. The results of the correlation test found that there was a relationship between the incidence of bullying and the assertive behavior of high school students. This relationship is not unidirectional and strong enough (rs = - 0.692), meaning that if the bullying is reduced, assertive behavior will increase. Further researchers are expected to be able to examine other factors that cause bullying, such as bullying at school.